Enhancing Portability and Confidentiality of Data Migration Among Inter Clouds - Kaur, Gagandeep; Kaur, Kiranbir (International Journal of Computer Sciences and Engineering, 2018)
Transferring information over the network is widely used fast and reliable source for communication. Users with wide fidelity use this mechanism for transferring and accessing information. Portability and interoperability within the cloud system through offline and online mediums are continuously desirable but the problem of security arises during the transmission process. Security and reliability is the key issue during the transfer process which is considered in this research. Information security is provided using the public and private key RSA cryptography. The experiment is implied not only at offline data but also at online data such as Google Docs. Redundancy handling mechanism is used to ensure that space at data storage provider is least used since cost in DSP is accompanied by the amount of storage used. Overall space requirement in case of heavy files is reduced and security of online information accessing is enhanced by the use of RSA cryptography with redundancy handling mechanism.